2019
DOI: 10.1080/22221751.2019.1611346
|View full text |Cite
|
Sign up to set email alerts
|

SMRT sequencing revealed the diversity and characteristics of defective interfering RNAs in influenza A (H7N9) virus infection

Abstract: Influenza defective interfering (DI) particles are replication-incompetent viruses carrying large internal deletion in the genome. The loss of essential genetic information causes abortive viral replication, which can be rescued by co-infection with a helper virus that possesses an intact genome. Despite reports of DI particles present in seasonal influenza A H1N1 infections, their existence in human infections by the avian influenza A viruses, such as H7N9, has not been studied. Here we report the ubiquitous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
28
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 29 publications
5
28
1
Order By: Relevance
“…Analysis of DelVG sequences has provided contradictory information about the importance of complementarity at DelVG deletion junctions. Two recent studies reported the presence of overlapping sequences at the flanking regions of IV DelVG junction sites [17,18]. In contrast, we and others failed to detect a significant enrichment of overlapping sequences at the junction sites of many DelVGs [19,20].…”
Section: Plos Pathogenscontrasting
confidence: 99%
“…Analysis of DelVG sequences has provided contradictory information about the importance of complementarity at DelVG deletion junctions. Two recent studies reported the presence of overlapping sequences at the flanking regions of IV DelVG junction sites [17,18]. In contrast, we and others failed to detect a significant enrichment of overlapping sequences at the junction sites of many DelVGs [19,20].…”
Section: Plos Pathogenscontrasting
confidence: 99%
“…However, we have definitively shown that a pathogenic alphavirus, CHIKV, forms D-RNAs with substantial incapacitating deletions in a mammalian host. Importantly, many of the recombination events we observed in vivo were similar to ones observed in vitro during early passages, suggesting that expression of sgD-RNAs is a programmed phenomenon with potential biological functions, recapitulating observations made with IAV (21).…”
Section: Discussionsupporting
confidence: 79%
“…For patients with A(H1N1)pdm09 virus infection, Saira et al showed that only the 5= or 3= end of the polymerase genes were abundant, with few reads in the internal region (28). Using long-read sequencing, we previously showed that Ͼ90% of the reads mapping to PB2, PB1, or PA were defective interfering (DI) sequences for patients with A(H7N9) virus infection (19). In this study, we designed primers and probes to target the 5= end of the PB2 gene because the number of reads at the 5= end of PB2 was much higher than at those of PA and PB1 for most patients.…”
Section: Discussionmentioning
confidence: 99%
“…For the evaluation of the detection of A(H7N9), a total of 10 A(H7N9)-positive specimens were included. These were collected from patients in Hong Kong from 2014 and 2017, and six were included in our previous study (19).…”
Section: Methodsmentioning
confidence: 99%